REVITALIZING RESEARCH IN THE JUNIOR HIGH SCHOOL PROGRAM: INPUTS FOR CURRICULUM DEVELOPMENT AND FACULTY DEVELOPMENT PROGRAM - Arrieta, Gilbert Santos; Marasigan, Arlyne C. (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
The study aims to find out the experiences and observations of teachers in teaching Research to Junior High School students. In particular, it wants to identify what needs to be enhanced in the research curriculum and faculty development program, particularly in terms of the knowledge and skills of research teachers and the other teachers in the junior high school department. It found out that students consider research a difficult subject that makes them less interested. Research theories and concepts appropriate for junior high school must be identified for curriculum revision. Teachers believed that they need to enhance their knowledge and skills and gain more experience in writing to become creative and confident research teachers. For teachers to be actively engaged in research, they have to be provided with training and workshops related to research and be strongly encouraged to do at least action research. The faculty development program may also include creating research mentors and the provision of opportunities for publication